2021
DOI: 10.1155/2021/9054152
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Relationship between Postural Control and Pain-Related Clinical Outcomes in Patients with Chronic Nonspecific Low Back Pain

Abstract: Objectives. To explore the relationship between postural control and pain-related clinical outcomes in patients with chronic nonspecific low back pain (cNLBP). Methods. Participants with cNLBP and healthy individuals were recruited. Muscle activities were recorded during internal and external perturbation tasks. Postural control capacity was assessed by muscle onset time and integrals of electromyography (iEMGs) of postural muscles during the phases of anticipatory postural adjustments (APAs) and compensatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…It has been demonstrated that an increasing delay in the latency of external oblique muscle activation is accompanied by an increased Oswestry Disability Index score in patients with chronic low back pain, which occurs when performing a rapid arm-raising task [ 51 ]. Pain-related disabilities in patients with NCLBP may be related to APA under endogenous and exogenous postural disturbances [ 52 ]. All these studies suggest that dysregulated APA onset in trunk muscles may be associated with pain-related dysfunction, but the relationship remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that an increasing delay in the latency of external oblique muscle activation is accompanied by an increased Oswestry Disability Index score in patients with chronic low back pain, which occurs when performing a rapid arm-raising task [ 51 ]. Pain-related disabilities in patients with NCLBP may be related to APA under endogenous and exogenous postural disturbances [ 52 ]. All these studies suggest that dysregulated APA onset in trunk muscles may be associated with pain-related dysfunction, but the relationship remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Low back pain (LBP) is becoming a growing socioeconomic burden (Hartvigsen et al, 2018;Cieza et al, 2021;Chiarotto and Koes, 2022) because it increases the risk of disability and contributes to poor mental health. Many studies have confirmed that pain-related disabilities and intensity were likely related to the altered structure and function of muscles in patients with CLBP (Emami et al, 2018;Yu et al, 2021). For example, when facing external disturbances or changes in sensory input, patients with CLBP show greater body sway velocity and area 10.3389/fnhum.2023.1085831 (della Volpe et al, 2006;Willigenburg et al, 2013;da Silva et al, 2018), delayed muscle activity (Knox et al, 2018) and altered spinal kinematics (Meier et al, 2019), which could accelerate spinal degeneration and muscle spasms, injuries, and fatigue.…”
Section: Introductionmentioning
confidence: 98%
“…LBP patients may suffer from certain degrees of postural control abnormalities, mainly manifested as decreased trunk coupling ability, 7 impaired gait, 8 increased center of gravity and center of mass deviation, 9 prolonged or disappeared preactivation time of postural muscles, 10 proprioceptive disturbances, 11 decreased attention and executive ability, 12 and reorganized structural or functional of the central nervous system. 13 …”
Section: Introductionmentioning
confidence: 99%